Education on Compliance with Drinking Blood Adding Tablets (Fe) as An Effort to Prevent Anemia in Adolescent Girls Of SMP I & SMA I in Syamtalira Bayu District - Usman, Hafsah; Fitriani, Aida; Fatiyani, Fatiyani (Pascasarjana Universitas Mataram, 2024)
The prevalence of anemia is quite high, so teenagers should pay more attention to their own health. Indonesia in 2019 showed that Aceh City was among the four provinces that had not met the target for providing TTD, amounting to 20.29%, while Indonesia nationally had a strategic plan target of 30%. The number of young women who do not consume or drink blood supplement tablets is unknown. There needs to be a more in-depth study of teenagers who consume Fe tablets. This is the first step to prevent anemia in young women. 307 young female students at SMA N I and SMP N I Syamtalira Bayu District were recorded, with the answer being that they never consumed TTD every week, but when they felt their bodies were weak, tired and felt dizzy. Purpose of Service; early detection of anemia by using a basic compliance questionnaire and providing education to young women from SMA N I and SMP N I in Syamtalira Bayu District. Devotion Method; This activity was carried out on female students at SMA N I and SMP N I in Syamtalira Bayu District, detecting them early using a basic compliance questionnaire and providing education to young women. Participants in this activity were 307 young women from SMP N I v Classes VII, VIII, IX and SMA Classes X, XI, XII aged 13-18 years. The implementation of this activity includes several stages, namely socialization (introduction), filling out a questionnaire and then providing education about the importance of taking Fe tablets during adolescence and how to take them.